KERAGAMAN DAN KELIMPAHAN JENIS KODOK SERTA HUBUNGANNYA DENGAN VEGETASI PADA LAHAN BASAH "ECOLOGY PARK", KAMPUS LIPICIBINONG - Hellen Kurniati (BERITA BIOLOGI, 2010)
Previous ecological studies have revealed the types of non-forest frog commonly occupying habitats that have been modified by humans are still severely limited. For that purpose the research was conducted in the wetland area of Ecology Park in LIPI Campus Cibinong which is located at S 06" 29' 40.2"; E 106° 51' 06.3" with 165 meters altitude above sea level (asl) over seven months (May-November 2009) by monitoring 14 times during the study period (July-November).The transect method was used to determine the effect of habitat on the diversity and abundance of frog species in the wetland area. Transect was set for 100 meters on one side of the lake where the area has a variety of habitat types. Length of 100 meters transect was divided into 10 sections with 10 meters length for each section, (length of each section was 10 meters). Every 10 meters, the type of habitat, frog species encountered and the abundance of the species were recorded. Environmental data recorded were air humidity, air temperature, water temperature and moon phase (full moon, crescent moon or the dark moon). Ten frog species which belong to 4 families, the Bufonidae (Bufo biporcatus and B. melanostictus), Microhylidae (Kaloula baleata), Ranidae (Fejervarya cancrivora, F. limnocharis, Rana chalconota, R. erythraea, R. nicobariensis and Occidozyga lima) and Rhacophoridae (Polypedates leucomystax) were found.R. erythraea, R. nicobariensis and O. lima were the dominant species and found on every visit. Furthermore, the most dominant species was R. erythraea. The results showed that environmental factors (air temperature, water temperature, humidity and conditions of the moon) did not have an impact on the presence and number of species. Abundance of three dominant species (R.erythraea, R. nicobariensis and O. lima) was strongly linked to vegetation type. Moreover, environmental factors (water temperature, humidity and the condition of moon) affected the abundance of R. nicobariensis in sub transect 2 and 5 where dominated by Eleocharis dutcis ans Leerxia hexandra. On the other hand air temperature affected the abundance of O.lima in sub transect 7, dominated by floating lotus plant Nymphaea lotus.